1996
DOI: 10.1021/tx950207j
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fluoro Substituents on Reactivity of 7-Methylbenz[a]anthracene Diol Epoxides

Abstract: The present study has examined potential mechanisms for the influence of F-substituents on the biologic activity of methylbenz[a]anthracenes. DNA adducts derived from reaction of the racemic bay-region anti-diol epoxides of 7-methylbenz[a]anthracene, and its 9- and 10- fluoro derivatives, with calf thymus DNA in vitro were partially characterized. All three hydrocarbon diol epoxides produced similar DNA adduct profiles upon reaction with calf thymus DNA in vitro that were composed of two deoxyganosine and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…Similar F-substitution effects were also observed for the 7-and 12-monomethyl analogues of BA [46,[50][51][52]. Effect of a fluoro substituent at C-9 and C-10 on tumorigenicity of 7-MBA-3,4-diol, 12-MBA-3,4-diol, and 7,12-DMBA-3,4-diol was also studied [51]. It was argued that F-substitution at C-10 in BA increases the metabolic formation of the 3,4-diol, with no significant effect on the reactivity of the bay-region anti-DE [51].…”
Section: Carbocations From Oxidized Metabolites Of Pahssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar F-substitution effects were also observed for the 7-and 12-monomethyl analogues of BA [46,[50][51][52]. Effect of a fluoro substituent at C-9 and C-10 on tumorigenicity of 7-MBA-3,4-diol, 12-MBA-3,4-diol, and 7,12-DMBA-3,4-diol was also studied [51]. It was argued that F-substitution at C-10 in BA increases the metabolic formation of the 3,4-diol, with no significant effect on the reactivity of the bay-region anti-DE [51].…”
Section: Carbocations From Oxidized Metabolites Of Pahssupporting
confidence: 71%
“…For other regioisomeric fluoro derivatives of 7,12-DMBA, there was no significant change in activity [44,47]. Similar F-substitution effects were also observed for the 7-and 12-monomethyl analogues of BA [46,[50][51][52]. Effect of a fluoro substituent at C-9 and C-10 on tumorigenicity of 7-MBA-3,4-diol, 12-MBA-3,4-diol, and 7,12-DMBA-3,4-diol was also studied [51].…”
Section: Carbocations From Oxidized Metabolites Of Pahssupporting
confidence: 56%
“…The 10-F derivative was less reactive than nonfluorinated 7-MBA, this fact being in contrast with the experimental tumorigenic activities. However, subsequent studies have suggested that the influence of fluorine at C-10 of BA is not due to increased reactivity of the bay-region DE but rather likely on the initial formation of the 3,4-diol (21). Both 10-F-7-MBA and 7-MBA afforded ΔE r s more exothermic than 9-F-7-MBA, in accord with the biological activity of these derivatives (16,(20)(21)(22).…”
Section: (3)mentioning
confidence: 87%
“…However, subsequent studies have suggested that the influence of fluorine at C-10 of BA is not due to increased reactivity of the bay-region DE but rather likely on the initial formation of the 3,4-diol (21). Both 10-F-7-MBA and 7-MBA afforded ΔE r s more exothermic than 9-F-7-MBA, in accord with the biological activity of these derivatives (16,(20)(21)(22). On the other hand, F-substitution at a position with negative charge density (C-5) decreased the exothermicity of the opening reaction, while 7-FBA also gave a less favored value than 7-MBA, both results being in agreement with their reported relative tumorigenicities (23,22).…”
Section: (3)mentioning
confidence: 87%
“…Also, substitution of an F-atom at C-11, the 'peri' position of 5-methylchrysene was found to reduce the tumour-initiating activity of the parent compound [52,63]. In contrast, markedly enhanced tumour-initiating and mutagenic activity was reported in case of fluorinated DMBA and 7-MBA containing a fluorine atom in C-10 position [64].…”
Section: Polycyclic Arenesmentioning
confidence: 99%